(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Iodine is an important micronutrient for mental growthand development. Limited information is available on the role of iodinesupplementation in pregnancy and its effect on perinatal outcome. We designedintervention study to assess the effect of iodine supplementation during secondhalf pregnancy and its effect on perinatal outcomes. An adequate iodine intake during pregnancy is essentialfor the synthesis of maternal thyroid hormones and normal brain development inthe fetus. Scant evidence is available on the effects and safety of iodinesupplementation during pregnancy in areas with adequate or mildly deficientiodine intake. Iodine is an essential constituent of thyroid hormones (TH). THactively take part in critical periods of brain development during embryonic,fetal and postnatal stages. Therefore the absence of TH or iodine in thesecritical periods produces an irreversible brain damage. In fact, it is knownthat iodine deficiency is the leading cause of preventable brain damageworldwide. Because of the physiological adjustments during pregnancy iodinerequirements increase significantly from 150 μg per day in non-pregnant adultwomen to 250 μg per day. Moreover, recent epidemiological studies around theworld show that iodine intake during pregnancy is insufficient in manycountries, even in developed countries like Australia, Spain and Italy. In thepresent work an overview of the importance of iodine nutrition during pregnancyis given.